Problematika Orang Tua Peserta Didik Dalam Bimbingan Belajar Dirumah Saat Pandemi Covid-19 Di Sdn Pindahan Baru Kecamatan Rantau Badauh: Problems Of Students' Parents In Student Guidance At Home During The Covid-19 Pandemic At SDN Pindahan Baru, Rantau Badauh District - Insaniyah; Inuriya Verawati; Aditya Hartini; Mahrita; Saidah Tunnoor (Tunas: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
This study aims to find out the problems of parents in guiding their children to study at home during the covid-19 pandemic at SDN Moving Baru. The research method used is a qualitative method. The population used in this study were some parents of grade I-VI students. The samples taken were 12 parents of students using random sampling technique. The data mining tools used were observation and interviews. The data processing technique used is data analysis of the Miles and Huberman models, namely data reduction, data presentation, and drawing conclusions. The results of the study, namely: 1) The work of parents increases, 2) Lack of mastery of the subject matter given by the teacher, 3) Difficult to grow children's interest in learning. Parents overcome these problems by: 1) Dividing time between work and guiding children to study at home, 2) Using cellphones, namely searching the Internet to find answers, 3) Inviting children to talk nicely or give a gift. From the results of the study, it can be concluded that parents get a problem in tutoring at home during the covid-19 pandemic.